2023
DOI: 10.1021/jacs.3c01113
|View full text |Cite
|
Sign up to set email alerts
|

One Atom Can Make All the Difference: Gas-Induced Phase Transformations in Bisimidazole-Linked Diamondoid Coordination Networks

Abstract: Coordination networks (CNs) that undergo gas-induced transformation from closed (nonporous) to open (porous) structures are of potential utility in gas storage applications, but their development is hindered by limited control over their switching mechanisms and pressures. In this work, we report two CNs, [Co(bimpy)(bdc)] n (X-dia-4-Co) and [Co(bimbz)(bdc)] n (X-dia-5-Co) (H 2 bdc = 1,4-benzendicarboxylic acid; bimpy = 2,5-bis(1H-imidazole-1-yl)pyridine; bimbz = 1,4-bis(1H-imidazole-1-yl)benzene), that both un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 79 publications
0
9
0
Order By: Relevance
“…Whereas grafting of functional groups onto linkers affects flexibility and sorption profiles, single atom substitution has little impact upon host structure yet can still profoundly impact flexibility and sorption profiles. Specifically, the “linker engineering” detailed herein, was found to modulate switching between flexible and ‘rigid‘ phases, rather than gate‐opening pressure and/or isotherm shape modification as seen previously for the same ligand pair [19b] . From a property perspective, the “memorized” α′ (open) phase induced by CO 2 sorption exhibited excellent CO 2 /N 2 (15/85) separation performance at 298 K and 1 bar, conditions that would be infeasible for the activated β (non‐porous) form.…”
Section: Discussionmentioning
confidence: 63%
“…Whereas grafting of functional groups onto linkers affects flexibility and sorption profiles, single atom substitution has little impact upon host structure yet can still profoundly impact flexibility and sorption profiles. Specifically, the “linker engineering” detailed herein, was found to modulate switching between flexible and ‘rigid‘ phases, rather than gate‐opening pressure and/or isotherm shape modification as seen previously for the same ligand pair [19b] . From a property perspective, the “memorized” α′ (open) phase induced by CO 2 sorption exhibited excellent CO 2 /N 2 (15/85) separation performance at 298 K and 1 bar, conditions that would be infeasible for the activated β (non‐porous) form.…”
Section: Discussionmentioning
confidence: 63%
“…21,22 There are also a few reports on the guest adsorption by nonporous crystals in the field of CPs. 19,20,[26][27][28][29][30] Studies on flexible metal-organic frameworks (MOFs) showed that the pore size would be enlarged when absorbing guest molecules. 31,32 They usually transform from narrow pores to larger pores, with only a few extreme examples transferring from nonporous to porous stages.…”
Section: Introductionmentioning
confidence: 99%
“…Modulating the solid-state property of thermal expansion (TE), which describes the response of a material to a change in temperature, is of utmost importance for fabricating materials with extraordinary performance. Depending on the intended application, specific TE behaviors are often required. For example, materials that exhibit large TE behavior are useful for thermomechanical actuators and sensors. On the other hand, materials that undergo smaller changes in response to temperature alterations are useful in ceramics and aerospace applications. , In the field of semiconductor and composite materials, the TE behavior of all the components needs to be adequately matched to avoid device failure when temperature changes occur. One significant challenge that materials scientists face lies in controlling a material’s structure, and this control is critical because structure directly influences properties. Control over solid-state structure is often accomplished by directing atomic or molecular self-assembly and packing in all dimensions. However, depending on the atomic or molecular building blocks, some dimensions may not be easily self-assembled with the assistance of strong interactions.…”
Section: Introductionmentioning
confidence: 99%